Analysis of Islamic Education Management for Inmates in Class IIb Correctional Institution Jambi Province - Ade Sofa; Mukhtar Mukhtar; Wahyudi Wahyudi (Edumaspul: Jurnal Pendidikan, 2024)
This study analyzes the management of Islamic education for inmates at the Class IIB Correctional Institution in Jambi Province. Islamic education plays a strategic role in the rehabilitation process, aimed at fostering spiritual and moral awareness among inmates and reducing recidivism rates. A qualitative descriptive approach was employed, using data collected through interviews, participatory observation, and document analysis. The findings reveal that the management of Islamic education is structured, encompassing stages from planning, implementation, to evaluation. Islamic education programs, including Quranic studies, hadith discussions, fiqh, and moral development, were found to effectively improve inmates' religious understanding and behavior. This study contributes to the development of more effective Islamic education management models in correctional institutions, supporting inmate rehabilitation.